Implications of ChatGPT implementation on students' understanding level in Pancasila Education subjects - Ismi Adnin; S. Sapriya; R. Rahmat; Abhi Rachma Ramadhan; Karlin Geriun Antonius Manik; Daffa Fakhri Maulana; Aland Aryaguna; Kireida Rona Islam; Muhammad Fajri Mubarok; Tebi Lesmana (Inovasi Kurikulum)
Learning requires supporting media to achieve the desired goals. The modern era makes technology an inseparable part of human life, including in the learning process in educational units. The technology that is currently developing rapidly is artificial intelligence (Artificial Intelligence), one of which is implemented in the form of the ChatGPT program. Currently, many students use ChatGPT to help them understand the subject matter, supported by the various conveniences offered by this technology. This study aims to provide an argumentative overview of the importance of utilizing technology, especially the ChatGPT program, in improving student understanding. The approach used in this study is qualitative with a descriptive method, which includes data and document analysis through the process of data reduction, data presentation, and drawing conclusions. In this study, the resource persons involved were 36 students in grade XI-4 at SMA Negeri 1 Tanjung Raja. The results of the study showed that the use of ChatGPT significantly helped improve students' understanding in the Pancasila Education subject, as well as supporting the achievement of educational goals such as critical thinking skills, creativity, and independent problem-solving skills.